An attempt to establish an inbred line of mice genetically resistant to Cowdria ruminantium - du Plessis, J L; Meyer, E H; van Gas, L (Onderstepoort journal of veterinary research, 1990)
An attempt to establish an inbred line of mice resistant to Cowdria ruminantium failed. First generation couples were constituted from those mice out of 100 males and 100 females that had survived infection with the Kümm stock of C. ruminantium and that were serologically negative to the indirect fluorescent antibody test. An attempt to establish 10 separate inbred lines by constituting next generation brother and sister matings from predominantly seronegative survivor mice from the preceding generation, was unsuccessful because too few mice survived the challenge. The percentage seronegative survivors increased to 94% over the first 6 generations, but then declined sharply during the next.